Optimax / Faridah Jusoh … [et al.] - Jusoh, Faridah; Ahmad, Nor Antasya; Mohamad Azmi, Nor Azilawati; Taibon, Zanariah (2003)
Optimax is a partnership company. Four members share this business. We will start our business by 2004. Optimax is located at lot 1-15, 1st floor, Alam Sentral Plaza, Jalan Majlis, Seksyen 14,40000 Shah Alam, Selangor Darul Ehsan. Our company will sell various types of spectacle and contact lens for all level ages. Beside that, our company also gives services like eyes checking, spectacle repair and free services for cleaning spectacle and eyes tips care. Our business site is located in strategic area which inside shopping complex Plaza Alam Sentral. We had chosen mis strategic site because it is the main shopping complex that many people visit especially UiTM students that are recognizing as our target market. The factors that influence our company to start up optical business because this sector is potential to expand in future and can make profit. Our business also gives special services to every customer compare with other shop spectacle. Furthermore our business is not only for bleary people but also for fashionable people. Our company has the higher potential to make profit in future. It is because demanding for spectacle and contact lens is higher between student and workers nowadays.